Suicide in teenagers during the COVID-19 pandemic in Cuba: actions for its prevention - Casamayor Leiza, Claudia Elvira; Pérez Yero, Julio César; Inerárity, Maydell Pérez; Miguel, Brayan Chávez (Journal of Community Medicine and Health Solutions, 2021)
Introduction: Suicidal behavior in teenagers constitutes a health problem that, given the necessary measures of social isolation taken by the global emergency of the COVID-19 pandemic, must generate timely actions for its prevention and control from the public health services. Objective: To propose an action plan for the prevention of suicide in teenagers of the Remedios municipality, subjected to voluntary home confinement during the COVID-19 pandemic. Methods: an observational, descriptive, cross-sectional study was carried out in the “XXX Anniversary” Teaching Community Polyclinic of the municipality Remedios. We worked with the population of 25 teenagers between 12 and 19 years old who made suicide attempts in the period 2019-2021. The empirical methods used were: bibliographic and documentary review, participant observation, focus group, semi-structured interview and questionnaire. Results: The suicide attempt was common in female teenagers aged 17 to 19 years not identified as risk, the lack of motivation due to the study activity and the previous suicide attempts by ingesting psychotropic drugs without serious intention of dying predominated. The most frequent psychological disorders were emotional disorders, stress, depression, irritability, apathy and insomnia. Actions are presented for the prevention of suicide and promote behaviors that contribute to mental health in the context of COVID-19. Conclusion: The prevention of suicidal behavior in teenagers in conditions of social isolation due to COVID-19, must include actions that facilitate the coping with stress, intra-family communication and resilience.